2012
DOI: 10.1111/j.1365-2966.2012.21473.x
|View full text |Cite
|
Sign up to set email alerts
|

The WiggleZ Dark Energy Survey: joint measurements of the expansion and growth history atz< 1

Abstract: We perform a joint determination of the distance–redshift relation and cosmic expansion rate at redshifts z = 0.44, 0.6 and 0.73 by combining measurements of the baryon acoustic peak and Alcock–Paczynski distortion from galaxy clustering in the WiggleZ Dark Energy Survey, using a large ensemble of mock catalogues to calculate the covariance between the measurements. We find that DA(z) = (1205 ± 114, 1380 ± 95, 1534 ± 107) Mpc and H(z) = (82.6 ± 7.8, 87.9 ± 6.1, 97.3 ± 7.0) km s−1 Mpc−1 at these three redshifts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
526
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 846 publications
(541 citation statements)
references
References 62 publications
12
526
0
3
Order By: Relevance
“…Other treatment improvements are described in [23]. To avoid possible correlations and to assure data independence, we also excluded the three data points from [40], at z = 0.44, z = 0.60 and z = 0.68, since the same data is used in our CMB/BAO analysis [15]. In our compilation we have also included two new measurements from cosmic chronometers at redshifts 1.363 and 1.965 from [24].…”
Section: H(z)mentioning
confidence: 99%
“…Other treatment improvements are described in [23]. To avoid possible correlations and to assure data independence, we also excluded the three data points from [40], at z = 0.44, z = 0.60 and z = 0.68, since the same data is used in our CMB/BAO analysis [15]. In our compilation we have also included two new measurements from cosmic chronometers at redshifts 1.363 and 1.965 from [24].…”
Section: H(z)mentioning
confidence: 99%
“…Figure 12. Constraints on f σ 8 from several redshift surveys in the base of ΛCDM, with f (z) = Ωm(z) γ : orange circle (6dFGRS by Beutler et al (2012)); gray triangle (SDSS Main Galaxy Sample by Howlett et al (2015)); green inverse triangle (SDSS Luminous Red Galaxies by Oka et al (2014)); cyan diamonds (WiggleZ by Blake et al (2012)); and purple pentagon (VIPERS by de la Torre et al (2013)). In red squares the results from BOSS-DR12 for the LOWZ and CMASS sample according to Table 3.…”
Section: Comparison With Other Galaxy Surveysmentioning
confidence: 99%
“…(iv) The WiggleZ analysis by Blake et al (2012) measures the galaxy correlation function and power spectrum. Considering both RSD and AP effects, they report f σ8 at 3 different redshifts, f (0.44)σ8(0.44) = 0.413 ± 0.080, f (0.6)σ8(0.6) = 0.390±0.063 and f (0.73)σ8(0.73) = 0.437± 0.072.…”
Section: Comparison With Other Galaxy Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…With this type of work, one typically compiles a unified sample of H(z) versus redshift measurements based on various approaches, including the determination of differential ages using cosmic chronometers (Moresco et al 2016b) and the inference of a characteristic distance scale revealed in baryon acoustic oscillations (BAOs; see, e.g. Blake et al 2012).However, it is inadvisable to make combined use of BAO measurements with other data. The BAO approach results in certain systematic effects that are difficult to quantify, certainly without the pre-assumption of a particular model.…”
mentioning
confidence: 99%